PERAN KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN - Budiarso, Novi S (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
This study explores the role of ownership and the relationship to the separation and control issue. Investigate the nature of agency cost generated by the existence of the ownership. The principal purpose of this study was to investigate the association between the ownership and dividend policy. This empirical study using regression model for the hypothesis testing. The sample consists of 34 firms by 4 subsectors in period of 2010-2011, which is listed in Indonesia Stock Exchange. The findings show that, partially, institutional ownership significantly influences dividend policy but the other side, public and managerial ownership not significantly influences to dividend policy. Simultaneously, institutional, public and managerial ownership influences dividend policy. The level and role of agency cost depends not only on ownership.